2013
DOI: 10.1371/journal.pone.0066380
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of TBE Incidence with Red Deer and Roe Deer Abundance in Slovenia

Abstract: Tick-borne encephalitis (TBE) is a virus infection which sometimes causes human disease. The TBE virus is found in ticks and certain vertebrate tick hosts in restricted endemic localities termed TBE foci. The formation of natural foci is a combination of several factors: the vectors, a suitable and numerous enough number of hosts and in a habitat with suitable vegetation and climate. The present study investigated the influence of deer on the incidence of tick-borne encephalitis. We were able to obtain data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 51 publications
1
27
0
1
Order By: Relevance
“…Analysis of the R 2 coefficients (Table ) reveals that the variability of the observed data is not fully explained by any considered model; therefore, we can assume that further influential factors were not taken into account. In particular, considering the importance of hosts in I. ricinus dynamics (Bolzoni et al , Jaenson et al , Jensen and Jespersen , Knap and Avšič‐Županc , Ostfeld et al ), the absence of the variable ‘Ungulates’ among the predictors included in the best models is somehow surprising. This is most likely due to the low quality of available data, rather than a supposed ecological irrelevance: in fact, these data refer to the municipality in which each sampling site lies and not to the specific sites and are determined by somewhat inaccurate methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the R 2 coefficients (Table ) reveals that the variability of the observed data is not fully explained by any considered model; therefore, we can assume that further influential factors were not taken into account. In particular, considering the importance of hosts in I. ricinus dynamics (Bolzoni et al , Jaenson et al , Jensen and Jespersen , Knap and Avšič‐Županc , Ostfeld et al ), the absence of the variable ‘Ungulates’ among the predictors included in the best models is somehow surprising. This is most likely due to the low quality of available data, rather than a supposed ecological irrelevance: in fact, these data refer to the municipality in which each sampling site lies and not to the specific sites and are determined by somewhat inaccurate methods.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, several environmental variables (both biotic and abiotic) that could influence ticks and tick‐borne pathogens have been investigated so far. Some examples of factors affecting tick abundance or the risk of disease transmission include climatic and meteorological conditions (Estrada‐Peña et al , Gern et al , Gray et al , Kiewra et al , Randolph , Randolph and Storey , Schulz et al ), vegetation type (Boyard et al , Jaenson et al , Tack et al ), topographic features, such as elevation, slope, and aspect (Gilbert , Jouda et al , Materna et al , Morán Cadenas et al ), and tick host species, particularly small mammals and deer (Bolzoni et al , Jaenson et al , Jensen and Jespersen , Knap and Avšič‐Županc , Ostfeld et al ). Studies regarding the relationship between ticks and environmental variables have already been carried out in the southern Alps (Carpi et al , Hudson et al , Merler et al , Nazzi et al , Rizzoli et al , , Tagliapietra et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The virus is transmit-ted to mammals, birds, reptiles and amphibians by ixodid ticks (Farkas, 2002;Weissenbock et al, 1998). It has been shown that the distribution area of Ixodes ricinus ticks, which are the principal vector for TBEV in Europe, is increasing (Gilbert, 2010;Medlock et al, 2013;Jaenson et al, 2012) due to climate changes (Rizzoli et al, 2009;Jaenson and Lindgren, 2011;Knap and Avšič-Županc, 2013) and/or anthropogenic factors (Randolph, 2004(Randolph, , 2010. It is known that the distribution rate of ticks and risk of tick-borne encephalitis (TBE) might be evaluated through analyses of the samples taken from wildlife or from animals, which are in close contact with humans (Paillard et al, 2015;Lindhe et al, 2009;Roelandt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of tick-borne diseases, such as Lyme borreliosis (LB) and tick-borne encephalitis (TBE), has increased over the last few decades in a number of European countries [ 1 3 ]. One explanation for the increase in tick-borne infections is that the distributional area and abundance of the principal vector, Ixodes ricinus, have increased [ 4 – 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In southern Sweden, the increase in the incidence of LB was positively correlated with a rise in monthly mean temperature [ 16 ]. Climate change could also influence the distribution and abundance of ticks and tick-borne diseases via indirect effects on vegetation [ 15 , 17 ] and important reservoir hosts like rodents [ 1 ]. The climate change hypothesis for the emergence of tick-borne diseases in Europe is controversial [ 2 , 7 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%